High-efficiency and high-luminance three-color white organic light-emitting diodes with low efficiency roll-off - Zhou, Junhong (2019)
For the first time, double blue emitting layers have been functioned as the main exciton generation zone to achieve high-performance three-color phosphorescent white organic light-emitting diodes (WOLEDs). The WOLED exhibits the maximum forward-viewing external quantum efficiency (EQE) and power efficiency (PE) of 21.2% and 50.0 lm/W, respectively. Even at 1000 c d / m2, the forward-viewing EQE and PE are as high as 18.0 % and 32.5 lm / W, respectively, indicating low efficiency roll-off. Besides, the WOLED shows a maximum luminance of 81156 c d / m2. Moreover, by manipulating the excitons distribution, a WOLED can achieve a high color rendering index of 80. The findings may provide a new opportunity to achieve high-efficiency, high-luminance and low efficiency roll-off WOLEDs.